(untitled) (Research, Society and Development, 2022)
Introduction: the concept of “Big Data” was defined by several authors, who described the different “Vs” that make up its definition. Over the years, more “Vs” have been incorporated; however, the basics include Volume, Velocity, Variety, Veracity, and Value. Objective: To analyze how the use of big data can contribute to the assistance of nurses in a basic health unit in Batalha - AL. Methodology: This is an intervention project, carried out by a high-level intern during the supervised curricular internship 1 of the bachelor’s degree in nursing at Faculdade UNIRB Arapiraca. Results: All objectives were achieved: creation of a database, creation of instruments for monitoring and mapping of the micro-area. Final Considerations: Therefore, collecting a large volume of data and mining Big Data is a very advantageous way to solve problems and plan care in prevention and health promotion in primary care.